Integridade superficial do aço-rápido AISI M3:2 após o processo de retificação - Vendrame, Saimon [UNESP] (2019)
High-Speed Steels are materials that exhibit high abrasive wear resistance coupled with relatively high toughness, properties that make them suitable for making cutting tools. Much of its properties are due to the presence of carbides in the microstructure. While these mechanical properties are favorable for use as tools, they impose challenges in their manufacture. The grinding process is employed in the final stages of the cutting tools manufacturing, such as taps and drills and the presence of carbides affects the efficiency of the grinding wheels. In this context, this work aims to investigate how the microstructure difference of class AISI M3: 2 steel, obtained from different suppliers, influences the grinding, taking into consideration the surface integrity. The materials, here named M-A, M-B, and M-C, were evaluated under three aspects: microstructure characteristics, abrasion resistance, and surface integrity after grinding. From the microstructure, carbides type MC and M6C were described regarding the shape and distribution, using for this purpose SEM and EDS. The abrasive wear resistance of the materials was measured using the pin-abrasive tribological test. After this characterization, flat tangential grinding tests were performed, using silicon carbide grinding wheel (SiC), in various work depths (between 10 μm and 30 μm). The ground samples surfaces were evaluated by measuring the roughness parameters, evaluated by SEM, and the microhardness profile near the surface was described. As a result, in the microstructure, the materials presented different morphologies and carbide distribution, and for the material, M-A presented the largest MC type vanadium carbides. The abrasive wear coefficient (k) for the three evaluated materials showed similar values (between 9.18 and 13.45 mm³.N-1.m-1), but the MA material presented abrasive wear instability (up to 28% variation between results). After grinding the surface of material M-C showed irregular scratches with material removal characteristics of fragile form. Was measured above-average microhardness (40% higher) in a layer up to 100 μm from the surface in the three materials sample in almost all conditions. These results are attributed to the effect of matrix brittleness and M6C carbides, which by fracturing result in fragile material removal.